Thoracoscopic radical surgery for a morbidly obese patient with early lung cancer after laparoscopic sleeve gastrectomy: a case report - Shingo Iwata; Akeo Hagiwara; Yutaka Harima (Surgical Case Reports)
Abstract Background We experienced a case of early stage lung cancer involving a morbidly obese patient. Obesity is associated with a higher incidence of surgical complications. We examined the effectiveness of laparoscopic sleeve gastrectomy as a primary weight loss procedure in a morbidly obese patient who required oncological surgery. Case presentation A 64-year-old morbidly obese female with a body mass index of 43.5 kg/m2 was referred to our hospital to undergo weight loss. A right-sided lung mass was found incidentally on computed tomography conducted in preparation for laparoscopic sleeve gastrectomy, which was performed prior to tumor surgery. As a result, weight loss was achieved within 2.5 months after the laparoscopic sleeve gastrectomy, and the patient’s type-2 diabetes, hypertension, and dyslipidemia, which are linked to obesity, were markedly ameliorated. After a quick intraoperative pathological inspection revealed that the tumor was malignant, thoracoscopic right lung superior lobe resection was performed safely. Conclusions Laparoscopic sleeve gastrectomy proved to be a powerful approach in a case in which a morbidly obese patient with early stage cancer needed to lose weight rapidly.